Kearifan Lokal Masyarakat Nelayan Skala Kecil Di Kelurahan Kuala Samboja Kecamatan Samboja Kabupaten Kutai Kartanegara: Kearifan Lokal Masyarakat Nelayan Skala Kecil Di Kelurahan Kuala Samboja Kecamatan Samboja Kabupaten Kutai Kartanegara - Rosa Marliza; Bambang Indratno Gunawan; Fitriyana (2339-1324, 2023)
ABSTRACT Rosa Marliza, 2022. Local Wisdom of Small-Scale Fishing Community in Kuala Samboja Village, Samboja District, Kutai Kartanegara Regency. (Supcivised by Bambang Indratno Gunawan and Fitriyana). The purpose of the study was to identify patterns of local wisdom and examine the problems of the small scale fishing communities in Kuala Samboja Village. Retrieval of research data in October 2021 in Samboja District, Kutai Kartanegara Regency. The research method used is descriptive qualitative. The results of the study obtained information on the pattern of local wisdom, namely the implementation of a sea party every year between October and November, ship safety, and the use of food resources at sea. Rules and taboos such as the awareness of the fishing community not to carry out fishing activities along a predetermined route; no fishing activity every Friday because it is used for resting and Friday prayers for the fishing community; not going to sea when a relative dies; or going to sea in bad weather. The fishing season for fishermen in January-April is the southern season which produces large catches, and May-August is the transition season for lack of catches. Techniques and technology using fishing gear such as fishing rods, trawl nets, and gillnet nets to find out the number of catches are to ask the previous people, see the cloudy water surface, the presence of fish jumping on the water surface, and carry out fishing activities, usually in the early morning until the afternoon. Some of the problems in the application of local wisdom are the prohibition of fishing locations, the prohibition of the use of fishing gear, and the seizure of fishing locations. Keywords: local wisdom, fishing, fishing community